조직재생을 위한 고분자 지지체의 최근 연구개발 동향 - 정윤기; 박기동; 박귀덕; 한동근 (대한의용생체공학회, 2008)
In tissue engineering, scaffolds play an important role in the growth of cells to 3-D organs or tissues. For the success of tissue engineering, they should be mimicked to meet the requirements of natural extracellular matrix (ECM) in the body, such as mechanical properties, adhesiveness, porosity, biodegradability, and growth factor release, etc. Contrary to other materials, polymeric materials are adequate to engineer scaffolds for tissue engineering because controlling the structure and the ratio of components and designing various shapes and size are possible. In this review, the importance, major characteristics, processes, and recent examples of polymeric scaffolds for tissue engineering applications are discussed.